Exploring Teaching Methods Used by the English Teachers in Teaching Speaking - Utami, Surti Nur; Wahyuni, Rina (SIGEH ELT : Journal of Literature and Linguistics, 2022)
This paper presents the findings of qualitative study aimed at exploring teachingmethod used by the English teachers to teach speaking. Speaking has always been as one ofchallenging skill for most students. The teachers have their own characteristic on applyingmethod to teach their students speaking skill which also suit with their students need. Thesample was the English teachers and students of SMA International Budi Mulia Dua at gradeXI. The data were collected from interviewing three English teachers and six students, as wellobserving the teaching process of speaking class. This result of this study revealed theteachers and students preference on the method which is applied during speaking class. Basedon the interview and classroom observation, there are some teaching methods that were usedby the teacher to teach the student speaking.